The efficacy of risk management strategies among dairy producers - Jimoh, Kunle Kodri (My University, 2025)
The United States dairy industry is a cornerstone of the agriculture economy, contributing significantly to rural livelihoods and the food system. However, it faces significant market volatility, fluctuating milk prices, and increasing input costs which threaten the financial stability of dairy producers. Effective risk management tools are critical to mitigating these risks and ensuring the sector's long-term sustainability. This study assesses the efficacy of Dairy Margin Coverage (DMC) as a risk management tool to mitigate the risk of price volatility. Based on the available data, we analyzed the DMC by applying program choices to historical (ex-post) data spanning from 2000 to 2024 across six regions (Illinois, Kansas, Michigan, Minnesota, Ohio, and Wisconsin). These treatments were compared to a control in which no risk management practices were adopted. Stochastic dominance and efficiency were used to compare the performance. The results of the risk management analysis show that DMC protects against and mitigates dairy farmer risks as it consistently reduces variances of dairy margins in Illinois, Kansas, Michigan, Minnesota, Ohio, and Wisconsin relative to the control of no risk management practices. Furthermore, dairy producers who elected a margin between $9.50 and $6.50 under the DMC program were better off in terms of lower income variance, as these coverage levels provided greater stability and reduced financial fluctuations compared to lower coverage levels or non-participation. The minimum coverage percentage and coverage level that yields a statistically significant difference in the Income Over Feed Cost relative to no risk management varies by state. Illinois, Michigan, Ohio, and Wisconsin have the minimum coverage rate, covering up to 35% of milk production at the $9.50 margin coverage level. Also, the result of our stochastic dominance shows that there is a statistically significant difference between DMC practices relative to no risk management practices at the upper levels of margin coverage and upper levels of production history coverage (75% to 95%). The analysis also reveals a gap between the program's expectations and practical outcomes, it shows a disconnect between the national DMC program and the state’s actual margins. The findings indicate that the program does not effectively provide payments when they are most needed but does pay out a good bit when it is not needed at the state level. These findings underscore the importance of tailoring the program to regional dynamics to enhance its effectiveness. This research provides critical insights for policymakers and stakeholders seeking to enhance the resilience and stability of the dairy industry through effective risk management strategies.
Keywords: Risk management; Dairy producer; Stochastic dominance; Operating margin; Dairy margin coverage